2018
DOI: 10.1002/smll.201803325
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Increase in Brightness and Singlet Oxygen Generation of an Organic Photosensitizer by Nanocrystallization

Abstract: Efficient organic photosensitizers are attractive for cancer cell ablation in photodynamic therapy. Bright fluorescent photosensitizers are highly desirable for simultaneous imaging and therapy. However, due to fundamental competition between emission and singlet oxygen generation, design attempts to increase singlet oxygen generation almost always leads to the loss of fluorescence. Herein, it is shown for the first time that nanocrystallization enables a simultaneous and significant increase in the brightness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…Notably, the aggregation process can also enhance the emission of PSs. Liu's group demonstrated that nanoparticles prepared by nanocrystallization increased the generation of singlet oxygen by a photosensitizer by 50 % and at the same time the fluorescence quantum yield more than doubled . The nanocrystals have been applied directly for HeLa cell ablation, and are found to be considerably more effective than their amorphous counterparts.…”
Section: Aie and The Research Branchesmentioning
confidence: 99%
“…Notably, the aggregation process can also enhance the emission of PSs. Liu's group demonstrated that nanoparticles prepared by nanocrystallization increased the generation of singlet oxygen by a photosensitizer by 50 % and at the same time the fluorescence quantum yield more than doubled . The nanocrystals have been applied directly for HeLa cell ablation, and are found to be considerably more effective than their amorphous counterparts.…”
Section: Aie and The Research Branchesmentioning
confidence: 99%
“…Additionally, crystallization is also regarded as an effective strategy to further elevate the fluorescence brightness and ROS generation efficiency of many AIEgens, as the packing degree of molecules increases to the maximum through crystallization, which remarkably minimizes the intramolecular motions. [ 74,75 ] Liu's group reported that the singlet oxygen ( 1 O 2 ) generation efficiency and fluorescence quantum yield (QY) of a PS could be elevated by 50% and over twofold at the same time after being fabricated into NPs through nanocrystallization method [76] . In addition, as a general and simple method to realize closer and ordered molecular packing, crystallization could also contribute to enhance the molar extinction coefficients with red‐shifted absorption maxima for some AIEgens [75] …”
Section: Aggregation‐induced Superiorities Of Aiegens In Theranosticsmentioning
confidence: 99%
“…Es ist dabei erwähnenswert, dass durch Aggregation auch die Emission von PS gesteigert werden kann. Die Gruppe um Liu demonstrierte, dass in Nanopartikeln, die durch Nanokristallisation erhalten wurden, die Erzeugung von Singulett‐Sauerstoff durch einen Photosensibilisator um 50 % gesteigert und zugleich auch die Quantenausbeute um mehr als das Doppelte erhöht wurde . Diese Nanokristalle wurden auch direkt zur Ablation von HeLa‐Zellen genutzt und erwiesen sich dabei als effektiver als die entsprechenden amorphen Materialien.…”
Section: Aie Und Die Verschiedenen Forschungszweigeunclassified